2013
DOI: 10.1068/b38093
|View full text |Cite
|
Sign up to set email alerts
|

Local Hedonic House-Price Modelling for Urban Planners: Advantages of Using Local Regression Techniques

Abstract: Hedonic house-price models have long been used in urban studies to investigate important factors characterizing cities (eg, the demand for amenities or housing submarkets). Traditionally, the formulation of hedonic models has been solved using global spatial econometric techniques. The development of local regression methods brought new insights into urban planning as the relationships between house prices and their determinants can be estimated locally and therefore mapped across space. Such maps provide plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Thus, by including longitude and latitude coordinates (ui, vi) to Eq. (1) above, the general form of the HPM can be mathematically expressed at location i in space as follows [Crespo and Grêt-Regamey 2013]…”
Section: The Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by including longitude and latitude coordinates (ui, vi) to Eq. (1) above, the general form of the HPM can be mathematically expressed at location i in space as follows [Crespo and Grêt-Regamey 2013]…”
Section: The Methodsmentioning
confidence: 99%
“…According to Eq. 2, the location-specific parameters βk (ui, vi) are estimated using weighted least squares and can be expressed as follows [Crespo and Grêt-Regamey, 2013]:…”
Section: The Methodsmentioning
confidence: 99%
“…In the real estate research, a number of studies have attempted to take advantage of GWR technique to investigate and appropriately modeled household demand for residential property attributes whether in general (for example, Lehner, 2011;McCord et al, 2012;Crespo and Grêt-Regamey, 2013) or specific terms such as public transport (for example, Du and Mulley, 2006;Banister, 2007;Dziauddin et al, 2015), road improvement (for example, Mulley, 2013), parks (for example, McMullen, 2011), environmental quality (for example, Carruthers and Clark, 2009) and neighbourhood quality (for example, Sunak and Madlener, 2012). In all of these studies, the authors report GWR performed better than OLS as indicated by a higher adjusted R 2 , a lower AIC and large differences in parameter estimates.…”
Section: Geographically Weighted Regression (Gwr) Approachmentioning
confidence: 99%
“…Since HPM provides a basis for GWR, by including longitude and latitude coordinates (u i , v i ) to the equation (1) above, the general form of a HPM can be mathematically expressed at location i in space as follows (Crespo and Grêt-Regamey, 2013: p. 667):…”
Section: Geographically Weighted Regression (Gwr) Approachmentioning
confidence: 99%
See 1 more Smart Citation